On Numerical Radius Bounds Involving Generalized Aluthge Transform. (10th January 2022) - Yan, Tao; Hyder, Javariya; Akram, Muhammad Saeed; Farid, Ghulam; Nonlaopon, Kamsing
Abstract : In this paper, we establish some upper bounds of the numerical radius of a bounded linear operator S defined on a complex Hilbert space with polar decomposition S = U ∣ S ∣, involving generalized Aluthge transform. These bounds generalize some bounds of the numerical radius existing in the literature. Moreover, we consider particular cases of generalized Aluthge transform and give some examples where some upper bounds of numerical radius are computed and analyzed for certain operators.